Characterization of a Multidrug-Resistant Salmonella enterica Serovar Heidelberg Outbreak Strain in Commercial Turkeys: Colonization, Transmission, and Host Transcriptional Response - Bearson, Bradley L.; Bearson, Shawn M. D.; Looft, Torey; Cai, Guohong; Shippy, Daniel C. (Frontiers in Veterinary Science, 2017)
In recent years, multidrug-resistant (MDR) Salmonella enterica serovar Heidelberg has been associated with numerous human foodborne illness outbreaks due to consumption of poultry. For example, in 2011, an MDR S. Heidelberg outbreak associated with ground turkey sickened 136 individuals and resulted in 1 death. In response to this outbreak, 36 million pounds of ground turkey were recalled, one of the largest meat recalls in U.S. history. To investigate colonization of turkeys with an MDR S. Heidelberg strain isolated from the ground turkey outbreak, two turkey trials were performed. In experiment 1, 3-week old turkeys were inoculated with 108 or 1010 CFU of the MDR S. Heidelberg isolate, and fecal shedding and tissue colonization were detected following colonization for up to 14-days. Turkey gene expression in response to S. Heidelberg exposure revealed 18 genes that were differentially expressed at 2 days following inoculation compared to pre-inoculation. In a second trial, 1-day old poults were inoculated with 104 CFU of MDR S. Heidelberg to monitor transmission of Salmonella from inoculated poults (index group) to naive penmates (sentinel group). The transmission of MDR S. Heidelberg from index to sentinel poults was efficient with cecum colonization increasing 2 Log10 CFU above the inoculum dose at 9 days post-inoculation. This differed from the 3-week old poults inoculated with 1010 CFU of MDR S. Heidelberg in experiment 1 as Salmonella fecal shedding and tissue colonization decreased over the 14 day period compared to the inoculum dose. These data suggest that young poults are susceptible to colonization by MDR S. Heidelberg, and interventions must target turkeys when they are most vulnerable to prevent Salmonella colonization and transmission in the flock. Together, the data support the growing body of literature indicating that Salmonella establishes a commensal-like condition in livestock and poultry, contributing to the asymptomatic carrier status of the human foodborne pathogen in our animal food supply.